Development of an Information System for Pool Villa Reservations - Chubour, Saowakon; Chupan, Areerat; Meedeach, Metaporn; Srikhiew, ์์Natnalin (Journal of Information and Learning [JIL], 2024)
This research aims to develop an information system for pool villa reservations and to study users' opinions on this system. The system development follows a design science research methodology comprising five steps: awareness of the problem, solution proposal, artifact development, artifact evaluation, and conclusion. The system's efficiency was evaluated using White-Box and Black-Box testing methods. The sample group consisted of 33 participants, including three business information system experts selected by purposive sampling and 30 system users, of whom 10 were pool villa owners selected by purposive sampling, and 20 were tourists selected by accidental random sampling. Data collection involved a system performance evaluation form and a user opinion questionnaire. Data analysis included content analysis, mean, and standard deviation. The research results showed that the web application of an information system for pool villa reservations comprised seven subsystems: basic information management system, user management system, villa data management system, booking management system, reporting system, customer support system, and search system. The experts agreed that the developed system was highly effective (M = 4.44, SD = 0.35). System users were highly satisfied (M = 4.38, SD = 0.60), and the technology acceptance of the system, based on the TAM model, was also at a high level (M = 4.46, SD = 0.49). The system has the potential to be commercially applied to pool villa businesses.